Spatial and Temporal Disparities of Leptospirosis Transmission in Sarawak (Malaysia), 2011-2018 - ROSDI KIRA; LESLEY MAURICE BILUNG; ROMANO NGUI; KASING APUN; LELA SU’UT (Borneo Journal of Resource Science and Technology, 2022)
This study is to analyse the spatial distribution of leptospirosis and identify its high and low incidence clusters in Sarawak. The annual incidence rate at the district level was calculated using confirmed report of leptospirosis cases from year 2011 to 2018. Empirical Bayes estimation smoothing of relative risks was used to display the spatial distribution of leptospirosis across the study region. Moran's Global Index and Local Indicators of Spatial Association (LISA) were used to analyse the existence of global and local spatial autocorrelation. Data were analysed using ArcGIS and Geoda software at the district level. The annualised average incidence reported during the study period was 20.83 per 100,000 population, with the highest cases reported in year 2018 (n = 870). The Global Moran's Index revealed spatial clustering of leptospirosis incidence in 2012 (Moran's I: 0.23), 2013 (Moran's I: 0.33), and 2014 (Moran's I: 0.45), while 2011 (Moran's I: -0.01), 2015 and 2016 (Moran's I: 0.09), 2017 (Moran's I: 0.13), and 2018 (Moran's I: 0.04) showed random patterns. High incidence clusters of leptospirosis were primarily congested in the Southeast of Sarawak, involving districts such as Kapit, Belaga, Song, Tatau and Lubok Antu. Spatial and temporal patterns of leptospirosis incidence were heterogeneous across Sarawak. This study facilitates the implementation of targeted interventions and control measures for leptospirosis in Sarawak by identifying spatial cluster and outliers.